Prevalence of MAFLD in the U.S. based on NHANES 2009–2018: differences in demographic characteristics, physical indices and lifestyle conditions - Dan Ye; Jiaofeng Wang; Jiaheng Shi; Yiming Ma; Yanglei Li; Qingshang Li; Xiaona Hu; Jie Chen; Zhijun Bao (BMC Gastroenterology)
Abstract Background The incidence of metabolic dysfunction-associated fatty liver disease (MAFLD) is high among U.S. adults, but studies on its occurrence in different ethnic and age groups are limited. The aim of the present study was to assess MAFLD occurrence among the U.S. adults by considering demographic characteristics, physical indices, and lifestyle conditions. Methods This study utilized the National Health and Nutrition Examination Survey (NHANES) data 2009–2018 from 23,546 participants aged ≥ 20 years. Variables such as age, sex, race, body mass index (BMI), waist circumference (WC), blood pressure, sedentary behavior, sleep, and depression were analyzed. Results Among 9933 participants, 3562 had MAFLD (34.1%), with notably higher percentages of Mexican-Americans (54.1%) and lower percentages of blacks (20.5%). The incidence of MAFLD was significantly greater (P < 0.001) in males (39%) than in females (29.2%), which was particularly evident within the 36–40 years age group. The MAFLD incidence exhibited an age-dependent pattern, initially increasing and subsequently declining (except for whites). Compared to white MAFLD patients, black MAFLD patients exhibited greater BMI, WC, systolic blood pressure (SBP), and diastolic blood pressure (DBP) values, whereas values for these measures were lower among Mexican–American patients. Logistic regression analysis adjusting for age and sex revealed that depression was more common among MAFLD patients (P < 0.001), except for severe depression (P > 0.05). Notably, the MAFLD incidence was not significantly associated with sedentary behavior or sleep duration. Conclusions The MAFLD incidence varies across different racial, age, and sex groups, and targeted interventions are essential for reducing the burden of MAFLD. However, further research is necessary to explore the correlations among MAFLD incidence, sleep patterns, and an inactive lifestyle.